Performance and Economic Suitability of Three Fast Growing Broiler Strains Raised Under Farming Condition in Bangladesh (International Journal of Agricultural Research, Innovation and Technology, 2013)
The performance and profitability of three commercial broiler strains reared under farming system were investigated in this study. Day-old broiler chicks (n=156) of three different commercial strains (Hubbard classic, Cobb-500 and MPK) were assigned to three treatment groups in a completely randomized block design, each treatment replicated four times, 13 birds per replicate. The birds were reared from d1 to 35 days of age with similar housing, feeding and environmental management condition. Regarding to all parameters collected, live weight and body weight gain were higher (P